Genetic based substitution techniques for audio steganography - Zamani, Mazdak (2010)
Steganography is a form of security technique through obscurity; the science and art of hiding the existence of a message between sender and intended recipient. Steganography has been used to hide secret messages in various types of files, including digital images, audio and video. The three most important parameters for audio steganography are imperceptibility, payload (bit rate or capacity), and robustness. Any technique which tries to improve the payload or robustness should preserve imperceptibility. The noise which is introduced due to bit modification would limit payload. This research focuses on audio steganography, particularly with respect to Waveform Audio File Format (WAV) files. The Least Significant Bit (LSB) is used as a type of substitution technique. In order to increase the payload and improve the imperceptibility, Genetic Substitution-Based Audio Steganography (GSBAS) was proposed. GSBAS is based on LSB and enhanced with the concept of genetic algorithm. GSBAS is benchmarked against Ordinary Substitution-Based Audio Steganography (OSBAS). The results showed that in comparison with OSBAS, the payload is considerably increased and Peak Signal-Noise Ratio (PSNR) is noticeably raised. The experiments showed that GSBAS gives promising result with high average payload and imperceptibility.